Enhancing Essential Oil Extraction from Lavandin Grosso Flowers via Plasma Treatment - Molina, Ricardo (2024)
This study explores the impact of plasma treatment on Lavandin Grosso flowers andits influence on the extraction of essential oils (EOs) via hydrodistillation. Short plasma treatmenttimes enhance the yield of EO extraction from 3.19% in untreated samples to 3.44%, correspondingto 1 min of plasma treatment, while longer treatment times (10 min) show diminishing returns to3.07% of yield extraction. Chemical characterization (GC/MS and ATR-FTIR) indicates that plasmatreatments do not significantly alter the chemical composition of the extracted EOs, preserving their aromatic qualities. Investigations into plasma–surface interactions reveal changes at the nanometer level, with XPS confirming alterations in the surface chemistry of Lavandin Grosso flowers by re- ducing surface carbon and increasing oxygen content, ultimately resulting in an increased presence of hydrophilic groups. The presence of hydrophilic groups enhances the interaction between the surface membrane of the glandular trichomes on Lavandin Grosso flowers and water vapor, conse- quently increasing the extraction of EOs. Furthermore, microscopic SEM examinations demonstrate that plasma treatments do not affect the morphology of glandular trichomes, emphasizing that surface modifications primarily occur at the nanoscale. This study underscores the potential of plasma technology as a tool to enhance EO yields from botanical sources while maintaining their chemical integrity.